Frailty and Fall Risk in Older Adults with Type 2 Diabetes: A Cross-Sectional Study - Yılmaz, Hatice; Çıray, Nazmiye (UI Scholars Hub, 2026)
Background: This study aimed to examine the effect of frailty on the risk of falls in older adults aged 65 years with type 2 diabetes. Methods: The study is cross-sectional and correlational. The sample included 146 individuals aged 65 years who had type 2 diabetes and visited the internal medicine outpatient clinic of a state hospital in Türkiye. The participants were assessed based on a personal information form, the Mini-Mental State Examination, Edmonton Frail Scale, Morse Fall Scale, and Katz Index of Independence in Activities of Daily Living. IBM SPSS Statistics version 22.0 was used for data analysis. Results: The mean frailty score was 5.59 ± 3.46, and 35.6% of the participants were not frail. The mean falls risk score was 45.65 ± 26.07, with a high risk of falls in 43.2% of the participants. The level of frailty, ADL score, participant age, and use of drugs other than diabetes medications explained 71.8% of the variation in the risk of falls (ß = 0.492; p < 0.001; R2 = 0.718). Conclusions: Frailty is positively associated with the risk of falls among individuals ≥ 65 years with type 2 diabetes mellitus.